The importance of metrics in a logistic company: Quality vs quantity (2022)
In this paper, I show my experience in Lean Solutions Group company for a year, as well as the responsibilities and duties that allowed the analysis of the difficulties of being a bilingual logistics coordinator as well as the strengths, weaknesses, and essential company information. In addition, this present work aims to illustrate and analyze a problem related to the daily goals and metrics required during my work and a methodology to increase my metrics by adding extra information. Based on the observations, analysis of the environment, and my personal experience, I will reflect on quantity and quality and their importance in Lean Staffing, as well as show the results after implementing a plan, an analysis, and some conclusions. Keywords: daily goals, quality, quantity, logistics coordinator, metrics.